Kemampuan Perbankan Syariah Dalam Mengoptimalkan Eksistensi Pada Era Digital 4.0 - Ade Syafitri; M. Irwan Padli Nasution (MES Management Journal, 2023)
This study aims to analyze the capabilities possessed by Islamic banking institutions in Indonesia to maintain their existence in the current era. Islamic banking in Indonesia has the potential to maintain its existence in the digital era, namely with human resource skills and making the most of existing technology through the existence of fintech. This is library research. The type of secondary data used in this study is in the form of library information for reading and recording online books, journals, and scientific articles. The results of the research are that the challenges that exist in the digital era now need to be faced by increasing the skills of Indonesian workers to understand the use of IOT (internet of things) technology in industry and using digital technology to understand competitiveness and increase productivity, technological innovation in banking products, as well as the use of digital technology by industry players. Keywords: ability, Existence, Islamic Banking